Pengaruh Penggunaan Media Pembelajaran Berbasis Digital Aplikasi Kahoot dan Motivasi Belajar terhadap Minat Belajar Siswa Kelas V SD Katolik 03 Frater Don Bosco Manado (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the effect of using digital-based learning media, the Kahoot application, and learning motivation on the learning interests of fifth-grade students at SD Katolik 03 Frater Don Bosco Manado. The study used a quantitative approach with a non-probability sampling method, a saturated sampling technique, involving 75 students as samples. The data were analyzed using descriptive statistics, correlation, reliability, normality, linearity, simple regression, and multiple regression with the help of SPSS 25. The results of the study showed that: (1) there was a significant direct effect of digital-based learning media, the Kahoot application, on students' learning interests with a significance value of p = 0.000